Optimising soluble protein expression in intein-originating fusion proteins. - Manoharan, Imayavan Manohar. (2013)
The need for alternate antibiotics is a burning problem currently due to the increasing resistance among microorganisms against existing antibiotics. Antimicrobial peptides are potential candidates as recent studies have shown little resistance among microorganisms. However, large scale economical production of good quality anti-microbial peptides is necessary to answer questions regarding the efficacy and safety of AMPs before launching it for therapeutic applications. Recombinant protein technology offers the opportunity to produce proteins in a large scale. One strategy is to produce the desired protein as a fusion protein and cleaving the target protein later chemically or enzymatically. Among the various fusion protein carriers, Intein – originating fusion proteins constructed using IMPACT (Intein-Mediated Purification with an Affinity Chitin-binding Tag) system from New England Biolabs (NEB) was tested in this project for its robustness and stability. For easier downstream processing and higher probability of getting the protein in bioactive form, soluble expression of protein is generally desired. This project aims to optimize the soluble protein expression of two Intein – originating fusion proteins containing two anti-microbial peptides named P11-5 and P2CN in E.coli. Cell culture conditions such as media composition and post induction incubation time were optimized. Moreover, 90% of the fusion proteins expressed using optimized cell culture conditions bound effectively to the chitin beads. Also, a final yield of 68 μg of pure P11-5/ 1 L of cell culture was obtained with optimized expression conditions.